INOVASI SEDERHANA, DAMPAK MAKSIMAL: PENGUATAN IDENTITAS USAHA DAN DIGITALISASI PEMBAYARAN PADA SALAH SATU UMKM KULINER DI JALAN RAPPOCINI RAYA - Andriani, Shadry; Regina; Abdur-Rabb, Ahmad Faqhruddin; Iksan Yusuf, Laode Muhammad; Parawansa, Ayu Kartini (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy but still face limitations in strengthening business identity and utilizing digital technology, especially in payment systems. This study aims to analyze the implementation of simple innovations through strengthening business identity and payment digitalization in a culinary MSME located on Rappocini Raya Street. The research uses a qualitative approach with observation, interviews, and documentation techniques. The results show that strengthening business identity through banners, logos, price lists, and product stickers increases visibility and customer attraction. Furthermore, the implementation of QRIS digital payment systems improves transaction efficiency and expands market reach. These simple innovations have proven to provide a real impact on improving business competitiveness.